1998
DOI: 10.1046/j.1365-2427.1998.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of dippers,Cinclus cinclus(L.), in the acid‐sensitive region of Wales 1984–95

Abstract: 1. Dippers were surveyed along seventy‐four acid‐sensitive streams in upland Wales in 1984 and again in 1995. At forty‐eight of the sites, and in an additional twenty‐three to twenty‐nine adjacent catchments, changes in acid‐base status and macroinvertebrate communities were assessed. River habitat surveys (RHS) and GIS (Geographical Information System) provided information on habitat features. 2. pH means across all the sites were higher on average by 0.12 pH units in 1995 than 1984, accompanied by significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Numerous studies have revealed strong effects of acidification on most biotic compartments of freshwater ecosystems, from planktonic organisms (Almer et al 1974;Harvey et al 1981;Havens 1991), macrophytes (Grahn 1986), fish (Leivestad and Muniz 1976), amphibia (Horne and Dunson 1995), birds (Scheuhammer 1991;Buckton et al 1998) and even mammals (Glooschenko et al 1988;Mason and Macdonald 1989). More particularly, many researchers have focused on the effects of acidification on the composition and structure of macroinvertebrate communities (Sutcliffe and Carrick 1973;Hall et al 1980;Harriman and Morrison 1982;Sutcliffe and Hildrew 1989;Feldman and Connor 1992;Gue´rold et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed strong effects of acidification on most biotic compartments of freshwater ecosystems, from planktonic organisms (Almer et al 1974;Harvey et al 1981;Havens 1991), macrophytes (Grahn 1986), fish (Leivestad and Muniz 1976), amphibia (Horne and Dunson 1995), birds (Scheuhammer 1991;Buckton et al 1998) and even mammals (Glooschenko et al 1988;Mason and Macdonald 1989). More particularly, many researchers have focused on the effects of acidification on the composition and structure of macroinvertebrate communities (Sutcliffe and Carrick 1973;Hall et al 1980;Harriman and Morrison 1982;Sutcliffe and Hildrew 1989;Feldman and Connor 1992;Gue´rold et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The biological responses to chemical change have also been investigated across a range of spatial and temporal scales, and with respect to different groups of organisms (Battarbee et al, 1988;Edwards et al, 1991;Juggins et al, 1996;Lancaster et al, 1996;Buckton et al, 1998). Disentangling the effects of long-term and short-term changes at different spatial scales, however, has proved extremely difficult (Ormerod and Jenkins, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed territory mapping combined with general use of the binomial model is a sensitive tool for environmental managers or scientists and may serve different objectives: (i) simple assessment of population size, (ii) long‐term assessment of variations in annual size of the population, or general trends (Marchant & Hyde 1980, Saether et al . 2000) or (iii) modelling of bird abundance in relation to habitat quality (Rushton et al . 1994, Buckton et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the White‐throated Dipper Cinclus cinclus (hereafter: Dipper) is one of the most widely studied, especially in Europe (Spitznagel 1985, Tyler & Ormerod 1994). This species has proved valuable for assessing responses to acidification (Buckton et al . 1998) and river regulation (D’Amico et al .…”
mentioning
confidence: 99%